Efficiency and Reliability of Reverse Osmosis Desalination Systems - A. F. Al-Dulaimi, Ayad (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
This study is concerned with the evaluation of the effect of Euphrates River water quality in Al-Samawa region during the period 1984-2003 on efficiency and reliability of reverse osmosis desalination systems by calculating the calcium sulfate scaling index depending on the following indicators: - TDS, Ca+2, Mg+2, Na+1, Cl-1, So4-2, HCO3-1. It was found from data analysis that this index for these units is greater than permissible limit. Also, the fitted relationship between this index and TDS is logarithmic, i.e. this index varies more rapidly than TDS, and consequently it is more representative to the water quality than TDS.